Clinical significance and biological roles of lncRNA CTBP1-AS in polycystic ovary syndrome - Li Qin; Chun Tian; Liying Huang; Xiao Qin; Shaohua Ling; Jingxi Wei; Bingsheng Huang; Lining Li; Xiaoqiong Luo (Journal of Ovarian Research)
Abstract Polycystic ovary syndrome (PCOS) is among the most prevalent endocrine and metabolic disorders affecting women of reproductive age. Multiple factors, including genetic predisposition, environmental influences, and lifestyle choices, are considered significant contributors to the development of PCOS. A kind of long noncoding RNA—C-Terminal binding protein 1 antisense (lncRNA CTBP1-AS) has been proven to be a new androgen receptor regulator. Previous studies showed that the lncRNA CTBP1-AS gene was highly expressed in a small sample of PCOS patients and was associated with the risk of PCOS, but its specific function and mechanism have not been clearly reported. In this study, the expression of lncRNA CTBP1-AS was detected by real-time quantitative PCR (RT-qPCR) in PCOS patients. In addition, lncRNA CTBP1-AS was overexpressed in KGN cells to explore its effect on granulocyte function. The results showed that the expression levels of lncRNA CTBP1-AS were increased in peripheral blood mononuclear cells and follicular fluid granulosa cells of PCOS patients compared with controls, which correlated with androgen levels and sinus follicle number; overexpression of lncRNA CTBP1-AS increased apoptosis and decreased cell migration ability, thus promoting the progression of PCOS. This study explores new biomarkers and therapeutic targets for the clinical individualized diagnosis and treatment of PCOS.